Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3354/dao03128
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with white spot syndrome virus outbreaks in marine shrimp farms in Rayong Province, Thailand

Abstract: The purpose of this study was to determine risk factors for white spot disease (WSD) in Rayong, Thailand. A study was conducted from October 2014 to March 2015 to identify potential farm-level risk factors using a validated questionnaire. We completed 1 questionnaire for each farm; a total of 38 questionnaires from the case farms and 127 questionnaires from the control farms were collected. The results showed that the presence of WSD in previous crops and the use of seawater were risk factors (p < 0.01), indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Generally, farmers need to add water during cultivation; hence, they use water directly from natural reservoirs or reservoir ponds, increasing the risk of WSD occurrence through untreated water. This result is consistent with our previous study, indicating that water added without treatment during ponding is a major risk factor ( Yaemkasem et al, 2017 ). In contrast, a closed recirculation system can reduce the risk of WSD more than an ordinary closed system; however, the operation of this system is more expensive.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Generally, farmers need to add water during cultivation; hence, they use water directly from natural reservoirs or reservoir ponds, increasing the risk of WSD occurrence through untreated water. This result is consistent with our previous study, indicating that water added without treatment during ponding is a major risk factor ( Yaemkasem et al, 2017 ). In contrast, a closed recirculation system can reduce the risk of WSD more than an ordinary closed system; however, the operation of this system is more expensive.…”
Section: Discussionsupporting
confidence: 94%
“…In the structured interview schedule, questions included those on farm information, farm practices, farm biosecurity, and possible risk factors associated with WSD ( Supplement 2 ). All questions were designed based on literature reviews ( Piamsomboon, Inchaisri & Wongtavatchai, 2015 ; Yaemkasem et al, 2017 ). In detail, the questions adopted from Piamsomboon, Inchaisri & Wongtavatchai (2015) were those related to farm area, culture area, number of pondings, water reserve area, source of farming water, owner of multiple farms, adjacent farms, water management, and application of fertilizer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, filtering the water before filling up culture ponds will prevent the entry of species that could be disease carriers [ 10 ]. Researchers have reported that in Thailand, sourcing water from communal canals, culturing shrimp year-round, a single owner operating more than one farm, the presence of WSD in previous crops, and the use of seawater were associated with WSD [ 11 , 12 ]. Studies in Rayong Province, Thailand, between October 2015 and September 2018 reported significant disease clustering in ponds near the sea [ 13 ].…”
Section: Introductionmentioning
confidence: 99%